Phenology of grassland plants responds to urbanization - Tina Christmann; Ingo Kowarik; Maud Bernard-Verdier; Sascha Buchholz; Anne Hiller; Birgit Seitz; Moritz von der Lippe (Urban Ecosystems, 2023)
Understanding phenological responses of plants to changing temperatures is important because of multiple associated ecological consequences. Cities with their urban heat island can be used as laboratories to study phenological adaptation to climate change. However, previous phenology studies focused on trees and did not disentangle the role of micro-climate and urban structures. We studied reproductive phenology of dry grassland species in response to micro-climate and urbanization in Berlin, Germany. Phenological stages were recorded weekly at the individual plant level for five native grassland species across 30 dry grassland sites along an urbanization and temperature gradient. We estimated 50% onset probabilities for flowering and seed maturation of populations, and analysed variation in onset dates using regression models. Early flowering species significantly advanced flowering phenology with increasing mean air temperature but were little influenced by urbanization. By contrast, late-flowering species showed significant phenological responses to both air temperature and urbanization, possibly because micro-climate was most affected by urbanization in late summer. Surprisingly, not all grassland species showed an advanced phenology with increasing intensity of urbanization. This contradicts observed patterns for urban trees, indicating that phenological shifts in urban areas cannot be generalized from the observation of one growth form or taxonomic group. Growth form appears as a possible determinant of phenological responses. Results suggest that the phenology of dry grassland species may directly respond to the urban heat island, albeit with variable direction and magnitude. This has implications for ecosystem services, shifted allergy seasons, changes of biogeochemical cycles and potential ecological mismatches.

Grassland allergenicity increases with urbanisation and plant invasions - Maud Bernard-Verdier; Birgit Seitz; Sascha Buchholz; Ingo Kowarik; Sara Lasunción Mejía; Jonathan M. Jeschke (Ambio, 2022)
Pollen allergies have been on the rise in cities, where anthropogenic disturbances, warmer climate and introduced species are shaping novel urban ecosystems. Yet, the allergenic potential of these urban ecosystems, in particular spontaneous vegetation outside parks and gardens, remains poorly known. We quantified the allergenic properties of 56 dry grasslands along a double gradient of urbanisation and plant invasion in Berlin (Germany). 30% of grassland species were classified as allergenic, most of them being natives. Urbanisation was associated with an increase in abundance and diversity of pollen allergens, mainly driven by an increase in allergenic non-native plants. While not inherently more allergenic than native plants, the pool of non-natives contributed a larger biochemical diversity of allergens and flowered later than natives, creating a broader potential spectrum of allergy. Managing novel risks to urban public health will involve not only targeted action on allergenic non-natives, but also policies at the habitat scale favouring plant community assembly of a diverse, low-allergenicity vegetation. Similar approaches could be easily replicated in other cities to provide a broad quantification and mapping of urban allergy risks and drivers.

Land sharing between cultivated and wild plants: urban gardens as hotspots for plant diversity in cities - Birgit Seitz; Sascha Buchholz; Ingo Kowarik; Johann Herrmann; Leonie Neuerburg; Julian Wendler; Leonie Winker; Monika Egerer (Urban Ecosystems, 2022)
Plant communities in urban gardens consist of cultivated species, including ornamentals and food crops, and wild growing species. Yet it remains unclear what significance urban gardens have for the plant diversity in cities and how the diversity of cultivated and wild plants depends on the level of urbanization. We sampled plants growing within 18 community gardens in Berlin, Germany to investigate the species diversity of cultivated and wild plants. We tested species diversity in relation to local and landscape-scale imperviousness as a measure of urbanity, and we investigated the relationship between cultivated and wild plant species within the gardens. We found that numbers of wild and cultivated plant species in gardens are high – especially of wild plant species – independent of landscape-scale imperviousness. This suggests that all community gardens, regardless of their urban contexts, can be important habitats for plant diversity along with their role in urban food provision. However, the number of all species was negatively predicted by local garden scale imperviousness, suggesting an opportunity to reduce imperviousness and create more habitats for plants at the garden scale. Finally, we found a positive relationship between the number of cultivated and wild growing species, which emphasizes that community gardens present a unique urban ecosystem where land sharing between cultivated and wild flora can transpire. As the urban agriculture movement is flourishing worldwide with gardens continuously and spontaneously arising and dissipating due to urban densification, such botanical investigations can support the argument that gardens are places for the reconciliation of plant conservation and food production.

A multidimensional framework for measuring biotic novelty: How novel is a community? - Conrad Schittko; Maud Bernard‐Verdier; Tina Heger; Sascha Buchholz; Ingo Kowarik; Moritz von der Lippe; Birgit Seitz; Jasmin Joshi; Jonathan M. Jeschke (Global Change Biology, 2020)
Anthropogenic changes in climate, land use, and disturbance regimes, as well as introductions of non‐native species can lead to the transformation of many ecosystems. The resulting novel ecosystems are usually characterized by species assemblages that have not occurred previously in a given area. Quantifying the ecological novelty of communities (i.e., biotic novelty) would enhance the understanding of environmental change. However, quantification remains challenging since current novelty metrics, such as the number and/or proportion of non‐native species in a community, fall short of considering both functional and evolutionary aspects of biotic novelty. Here, we propose the Biotic Novelty Index (BNI), an intuitive and flexible multidimensional measure that combines (a) functional differences between native and non‐native introduced species with (b) temporal dynamics of species introductions. We show that the BNI is an additive partition of Rao's quadratic entropy, capturing the novel interaction component of the community's functional diversity. Simulations show that the index varies predictably with the relative amount of functional novelty added by recently arrived species, and they illustrate the need to provide an additional standardized version of the index. We present a detailed R code and two applications of the BNI by (a) measuring changes of biotic novelty of dry grassland plant communities along an urbanization gradient in a metropolitan region and (b) determining the biotic novelty of plant species assemblages at a national scale. The results illustrate the applicability of the index across scales and its flexibility in the use of data of different quality. Both case studies revealed strong connections between biotic novelty and increasing urbanization, a measure of abiotic novelty. We conclude that the BNI framework may help building a basis for better understanding the ecological and evolutionary consequences of global change.

Isolation and characterization of new microsatellites at the nm23-H1 and nm23-H2 gene loci and application for loss of heterozygosity (LOH) analysis - Markus Seifert; Birgit Theisinger; Matthias Engel; Thomas Seib; Gerhardt Seitz; Manfred Stolte; Karin Hilgert; C. Welter (Human Genetics, 1997)